Detoxification of Hydrogen Cyanide Acids (HCN) From Rubber seed (Hevea brasiliensis Mull. Arg) through some Physical Treatment As Fish Feed Ingredients - Sofwan Said Daulay; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was carried out on July until August 2013 in the Fish Nutrition Laboratory, Faculty of fisheries and Marine Science University of Riau, Pekanbaru. The purpose of this study was to remove HCN from rubber seed and See influence treatment of nutrients. so the rubber seeds can serve as fish feed constituents. This study used a Randomized Complete Design (RAL) with nine treatment three times in rreplication. R0 = Without treatment, R1 = Boiling rubber seeds open for 30 minutes, R2 = steaming open rubber seeds for 30 minutes, R3 = rubber seeds drying out under sunlight for 12 hours, R4 = rubber seed soaking in running water for 36 hours, R5 = combination of steaming open rubber seeds for 30 minutes and drying out for 12 hours, R6 = combination of soaking for 36 hours with steaming open for 30 minutes, R7 = combination of soaking rubber seed soaking in running water for 36 hours with an open boiling for 30 minutes, R8 = combination of Boiling rubber seeds open for 30 minutes and drying out for 12 hours with sun light. The result showed that combination of Boiling rubber seeds open for 30 minutes and drying out for 12 hours with sun light (R8) was the most effective way to decrease HCN content, and gave better quality of rubber seed meal for ruminant feed.Key words: Detoxification, HCN, Rubber Seed.Nutrients.